Dynamic Response of Sjögren Inlet Glaciers, Antarctic Peninsula, to Ice Shelf Breakup Derived from Multi-Mission Remote Sensing Time Series - Seehaus, Thorsten C.; Marinsek, Sebastián; Skvarca, Pedro; van Wessem, Jan M.; Reijmer, Carleen H.; Seco, José L.; Braun, Matthias H. (Frontiers in Earth Science, 2016)
The substantial retreat or disintegration of numerous ice shelves has been observed on the Antarctic Peninsula. The ice shelf in the Prince Gustav Channel has retreated gradually since the late 1980s and broke up in 1995. Tributary glaciers reacted with speed-up, surface lowering and increased ice discharge, consequently contributing to sea level rise. We present a detailed long-term study (1993-2014) of the dynamic response of Sjögren Inlet glaciers to the disintegration of the Prince Gustav Ice Shelf. We analyzed various remote sensing datasets to identify the reactions of the glaciers to the loss of the buttressing ice shelf. A strong increase in ice surface velocities was observed, with maximum flow speeds reaching 2.82±0.48 m d-1 in 2007 and 1.50±0.32 m d-1 in 2004 at Sjögren and Boydell glaciers respectively. Subsequently, the flow velocities decelerated, however in late 2014, we still measured approximately twice the values of our first observations in 1996. The Sjögren Inlet glaciers retreated 61.7±3.1 km² behind the former grounding line in 1996. For the glacier area below 1000 m a.s.l. and above the 2014 grounding (399 km²), a mean surface lowering of -68±10 m (-3.1 m a-1) was observed in the period 1993-2014. The lowering rate decreased to -2.2 m a-1 in the period 2012-2014. Based on the surface lowering rates, geodetic mass balances of the glaciers were derived for different time periods. A strongly negative mass change rate of -1.16±0.38 Gt a-1 was found for the area of all Sjögren Inlet glaciers (including the area above 1000 m a.s.l.) above the 2014 grounding line (559km2) for the earliest period (1993-2001). Due to the dynamic adjustments of the glaciers to the new boundary conditions the rate changed to -0.54±0.13 Gt a-1 in the period 2012-2014, resulting in an average mass change rate of -0.84±0.18 Gt a-1 (1993-2014) for the same domain. Including the retreat of the ice front and grounding line, a total mass change of -37.5±8.2 Gt (-1.79±0.39 Gt a-1) and a contribution to sea level rise of 20.9±5.2 Gt (-0.99±0.25 Gt a-1) were computed for the period 1993-2014. Analysis of the ice flux revealed that